Aquaporin-4 antibody-positive cases beyond current diagnostic criteria for NMO spectrum disorders. - Sato, D; Nakashima, I; Takahashi, T; Misu, T; Waters, P; Kuroda, H; Nishiyama, S; Suzuki, C; Takai, Y; Fujihara, K; Itoyama, Y; Aoki, M (2013)
OBJECTIVES: To analyze aquaporin-4 (AQP4) antibody-positive patients who do not fulfill the current diagnostic criteria of neuromyelitis optica (NMO) and NMO spectrum disorders (NMOSD). METHODS: We used a cell-based assay (CBA) with AQP4-transfected cells to detect AQP4 antibody in 298 consecutive patients with inflammatory CNS disorders seen at Tohoku University Hospital from 2007 to 2012. The patients were diagnosed as NMO, NMOSD, multiple sclerosis, or others using the respective current diagnostic criteria. The seropositive samples by CBA were also tested using a commercial ELISA. RESULTS: Seventy-two patients were AQP4 antibody positive. Among them, 18.1% (13/72) did not meet the NMO or NMOSD criteria (7 with monophasic optic neuritis, 2 with attacks restricted to the brainstem, and 4 with myelitis with less than 3 vertebral segments) and 84.6% (11/13) of these had only a single attack. The ELISA results were negative in 38.4% (5/13) of those patients, and they had lower antibody titers by CBA than patients with NMO/NMOSD. Although these patients had a shorter follow-up and few attacks, they shared some clinical features with NMO/NMOSD patients such as onset age, female predominance, presence of other autoantibodies, severe optic neuritis attacks, centrally located spinal cord lesions, persisting hiccups, and nausea or vomiting episodes. CONCLUSIONS: AQP4 antibody-positive patients with single or recurrent attacks of optic neuritis, myelitis, or brain/brainstem disease not fulfilling the current criteria of NMO or NMOSD may not be uncommon, and they should also be included in the NMO spectrum.